The 27th Chinese Control and Decision Conference (2015 CCDC) 2015
DOI: 10.1109/ccdc.2015.7162875
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of compound TCP with Random Early Detection (RED) queue management

Abstract: We study the performance of Compound TCP with Random Early Detection (RED) in three different limiting regimes. In the first regime, averaging over the queue size helps to decides the probability of dropping packets. Then, we consider a model where averaging over the queue size is not performed, but the queue is modelled as an integrator. Finally, we consider a model where the threshold for dropping packets is so small that it is not possible to model the queue as an integrator. In these three regimes, we deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…We have investigated these closed form expressions against our Markovian models in [38] and have found that the closed form expressions are not as accurate as the Markovian model results. In [39,40,41], the authors study the performance of TCP Compound using control theoretic techniques and derive stability conditions for TCP Compound. In these papers, it is shown that when multiple TCP flows share a single bottleneck queue, the queue sizes and the link utilization have oscillatory behaviour when the feedback delays (round trip times of the flows) and buffer sizes are large.…”
Section: Previous Studies Of Tcp Cubic and Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…We have investigated these closed form expressions against our Markovian models in [38] and have found that the closed form expressions are not as accurate as the Markovian model results. In [39,40,41], the authors study the performance of TCP Compound using control theoretic techniques and derive stability conditions for TCP Compound. In these papers, it is shown that when multiple TCP flows share a single bottleneck queue, the queue sizes and the link utilization have oscillatory behaviour when the feedback delays (round trip times of the flows) and buffer sizes are large.…”
Section: Previous Studies Of Tcp Cubic and Compoundmentioning
confidence: 99%
“…In [39], the authors evaluate the TCP Compound performance as a function of buffer size in the bottleneck queue. In [40], the authors study the performance of TCP Compound with a proportional integral enhanced queue management policy whereas in [41], RED queue management policy is considered.…”
Section: Previous Studies Of Tcp Cubic and Compoundmentioning
confidence: 99%
“…e authors studied the stability and bifurcation of compound TCP with the RED system in three different limiting regimes in [12,13]. In [14], chaotic phenomena and period doubling bifurcation of the first-order discrete time model for compound TCP with RED system are obtained by employing bifurcation diagrams and Lyapunov exponent.…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer analytical studies of TCP Compound as compared to the traditional AIMD variants. In [20][21][22], the authors study the performance of TCP Compound using control theoretic techniques and derive stability conditions for TCP Compound. In these papers, it is shown that when multiple TCP flows share a single bottleneck queue, the queue sizes and the link utilization has oscillatory behaviour when the feedback delays (round trip times of the flows) and the buffer sizes are large.…”
Section: Introductionmentioning
confidence: 99%
“…In [20], the authors evaluates TCP Compound performance as a function of buffer size in the bottleneck queue. In [21], the authors study the performance of TCP Compound with a proportional integral enhanced queue management policy whereas in [22], RED queue management policy is considered. In [23], the authors study the performance of a single TCP Compound connection in the presence of random losses using Markovian models.…”
Section: Introductionmentioning
confidence: 99%